Redesign, analysis, fabrication and testing of light weight fuselage, boom and empennage for solar UAV : Part 3 - Tan, Thomas Peng Ngee (2015)
Unmanned aerial vehicles (UAVs) have been gaining popularity in the recent years. Due to its ability to come in many different shapes and sizes allows it to be hard to detect and also the key aspect of a UAV is that there is no need for a physical pilot to be on board. Thus allowing it to perform search and rescue, surveillance and other tasks or missions that are too dangerous or unsuitable for a normal manned aircraft to perform. One of the main concerned or drawback of a UAV is its range. The range of UAVs are determined by their power source, and being a small aircraft there is a limit to how much fuel they can carry. Therefore with the in cooperation of solar modules onto UAVs, the range could be greatly increase as long as there is light. The aim of this Solar UAV project is to build a UAV with an endurance of at least 24 hours, fully power by solar energy for long range missions. As solar modules have to be both light weight and weather proof, the first part of this report will be focusing on solar encapsulation method and process, weight have to be kept down and also due to fragile nature of the solar cells, the process have to have the least damages cause during encapsulation to ensure high efficiency of the solar module. And the second part of this report will be on the selection of suitable aircraft and power plant for in cooperation of solar modules and key components needed for missions. It needs to be structurally strong enough to withstand the additional load from the solar modules and the various components needed for transmission of solar energy from solar cells to batteries, which includes the Maximum Power Point Tracking (MPPT) unit and also the Battery Management System(BMS). This final year project concludes the suitable encapsulation process and also the suitable aricraft and power plant. And the next phase of the project would be to construction solar modules for the selected plane with the in cooperation of auto pilot and telemetry to carry out pre-planned mission.